Pengaruh Transparansi Terhadap Kualitas Pelayanan Publik Pada Sistem Administrasi Manunggal Satu Atap Kota Gorontalo - Balada RAF (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2025)
This study aims to determine the effect of transparency on the quality of public services at the Gorontalo City One-Stop Manunggal Administration System (SAMSAT). The research employs a quantitative methodology. The population for this study comprises residents of Gorontalo City who have received services at the SAMSAT office, with a sample size of 30 individuals. The results of this research indicate that the influence of transparency on the quality of public services at the Gorontalo City SAMSAT is 63.8%. This finding can be categorized as a moderate level of influence. The study highlights a notable relationship between the two variables, suggesting that while transparency is a significant factor in service quality, it is not the sole determinant. These findings provide valuable insights for public administration, particularly in the context of government service delivery. The evidence supports the notion that increasing transparency can lead to improvements in public service quality. The study’s implications are relevant for policymakers seeking to enhance accountability and public satisfaction within administrative systems. Further research could explore other variables that contribute to service quality to gain a more comprehensive understanding.